The impact of unemployment on heart rate variability: the evidence from the Czech Republic - Jandackova, Vera K; Paulik, Karel; Steptoe, Andrew (Biological psychology, 2012)
We examined the relationship between unemployment and heart rate variability (HRV) in a region of high unemployment in the Czech Republic. The study involved 21 involuntarily unemployed and 21 employed men and women aged 30-49 years, matched on number of potentially confounding factors, including age, gender, type of job, health related behavior and body mass index. HRV was assessed in response to a modified orthostatic test. Compared with the employed group, unemployed participants had decreased high frequency HRV (p=0.018), lower root mean square of successive differences (p=0.050), and lower total spectral variability (p=0.022). These findings suggest that unemployment is a potential chronic stressor that may lead to suppression of vagal activity. This may be one mechanism linking unemployment with cardiovascular disease risk.
Keywords: dospělí; Female; autonomní nervový systém; Age Factors; Autonomic Nervous System; Adult; Unemployment; ženské pohlaví; věkové faktory; lidé; srdeční frekvence; Humans; Middle Aged; Sex Factors; zdravé chování; Male; sexuální faktory; Czech Republic; index tělesné hmotnosti; Health Behavior; Česká republika; lidé středního věku; mužské pohlaví; Body Mass Index; Heart Rate; nezaměstnanost